Effect of Risk Management on the Profitability of Nepalese Commercial Banks - Khatiwoda, Pallawi; Pokhrel, Prasiddha; Sah, Puja; Giri, Ranjana (Nepalese Journal of Business, 2025)
The study examines the effect of risk management on the profitability of Nepalese commercial. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are interest spread rate, loan loss provision, non-performing loan, capital adequacy ratio, bank size and loan to deposit ratio. The study is based on secondary data of 12 commercial banks with 120 observations for the period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, reports published by the Ministry of Finance and the annual report of respective banks. The correlation coefficients and regression models are estimated to test the significance and importance of liquidity risk, credit risk, and market risk on the profitability of Nepalese commercial banks. The study showed that interest spread rate has positive impact on return on assets and return on equity. It shows that increase in interest spread rate leads to increase in return on assets and return on equity. Similarly, loan loss provision has a negative impact on return on assets and return on equity. It implies that increase in loan loss provision leads to decrease in return on assets and return on equity. Moreover, non-performing loan has a negative impact on return on assets and return on equity. It shows that increase in non-performing loan leads to decrease in return on assets and return on equity. Similarly, capital adequacy ratio has a positive impact on return on assets and negative impact on return on equity. It means increase in capital adequacy ratio leads to increase in return on assets and decrease in return on equity. Likewise, bank size has a positive impact on return on assets and return on equity. It means that increase in bank size leads to increase in return on assets and return on equity. Furthermore, loan to deposit have a negative impact on return on assets and return on equity. It means that increase in loan to deposit leads to decrease in return on assets and return on equity.